Quantitative analysis of lncRNA in formalin-fixed paraffin-embedded tissues of oral squamous cell carcinoma - Kiran Kumar; Kaveri Hallikeri; Ajaykumar Oli; Mallikarjun Goni; Apoorva Jain; Jagadeesha Poyya; Alagilavada S Shilpasree; Palaksha Kanive Javaregowda (BioTechniques, 2023)
The study evaluated expression profiles of few regulatory lncRNAs in oral squamous cell carcinoma and normal mucosa adjacent to oral cancer using paired fresh frozen and formalin-fixed paraffin-embedded (FFPE) tissues stored at a different duration of time (1–5 years) using real-time quantitative PCR. The quantity and quality of total RNA isolated from FFPE tissues was less compared with that of fresh frozen tissues, which resulted in a noncorrelation of quantification cycle values. Following normalization, the expression of lncRNAs in the paired tissues did not differ significantly. The differential expression of the lncRNAs in the study was consistent with The Cancer Genome Atlas head and neck squamous cell carcinoma database. The study findings demonstrate the possibility of performing accurate quantitative analysis of lncRNAs using short amplicons and standardized real-time quantitative PCR assays in oral squamous cell carcinoma FFPE samples.